Mixed cropping of ginger (Zingiber officinale Rose.) and maize (Zea mays L.) - PETER, K KANDIANNAN, K M ABDULLA KOYA, K V (Journal of Spices and Aromatic Crops, 1999)
Ginger (Zingiber officinale Rosc., Zingiberaceae), a perennial herbaceous spice crop, is usually grown as an annual by small and marginal farmers in Kerala, West Bengal, Meghalaya, Karnataka, Sikkim and Mizoram in India.